The haemodynamic effects of umbilical cord milking in term infants: a randomised controlled trial - Mehmet Tekin; Mahmut Gokdemir; Erzat Toprak; Musa Silahli; Hasan Energin; Zeynel Gokmen (Singapore Medical Journal)
Introduction: Umbilical cord milking (UCM) is a method that allows for postnatal placental transfusion. The benefits of UCM have been demonstrated in some studies, but knowledge about its haemodynamic effects in term infants is limited. The aim of this study was to evaluate the haemodynamic effects of UCM in term infants. Methods: In this prospective, randomised controlled study, 149 healthy term infants with a birth week of ≥37 weeks were randomly assigned to either the UCM or immediate cord clamping (ICC) group. Blinded echocardiographic evaluations were performed in all the neonates in the first 2–6 h. Results: Superior vena cava (SVC) flow measurements were higher in the UCM group compared to the ICC group (132.47 ± 37.0 vs. 126.62 ± 34.3 mL/kg/min), but this difference was not statistically significant. Left atrial diameter (12.23 ± 1.99 vs. 11.43 ± 1.78 mm) and left atrium-to-aorta diastolic diameter ratio (1.62 ± 0.24 vs. 1.51 ± 0.22) were significantly higher in the UCM group. There were no significant differences in other echocardiographic parameters between the two groups. Conclusıon: We found no significant difference in the SVC flow measurements in term infants who underwent UCM versus those who underwent ICC. This lack of significant difference in SVC flow may be explained by the mature cerebral autoregulation mechanism in term neonates.